An evidence‐based medicine approach to small animal anaesthetic mortality in a referral practice: the influence of initiating three recommendations on subsequent anaesthetic deaths. (18th December 2013) - Bille, Christophe; Auvigne, Vincent; Bomassi, Eric; Durieux, Philippe; Libermann, Stéphane; Rattez, Elise
Abstract Objective To evaluate anaesthetic death after implementation of recommendations and its risk factors in a small animal practice. Study design Observational cohort study. Animals All cats and dogs anaesthetized at the Centre Hospitalier Vétérinaire des Cordeliers during two periods, from April 15th, 2008 to April 15th, 2010 (period 1) and from June 15th, 2010 to August 24th, 2011 (period 2). Methods Death occurring during or before full recovery from anaesthesia was recorded. At the end of period 1, a logistic regression model was generated to describe anaesthetic death and identify risk factors. Potential risk factors in our practice setting were identified, and three recommendations, relating to improving physical status and anaesthetic/analgesic regimen implemented for period 2. The relationship between anaesthetic death and recorded variables were analyzed, and where relevant, compared between periods. Results Six thousand two hundred and thirty‐one animals underwent general anaesthesia. The overall death rate during period 1 was 1.35% (48 in 3546, 95% CI [1.0–1.7%]) and during period 2 was 0.8% (21 in 2685, 95% CI [0.6–1.2%]). For sick animals (ASA status 3 and over), the overall death rate was 4.8% (45 of 944 95% [CI 3.5–6.4%]) during period 1 and 2.2% (18 of 834 95% CI [1.3–3.5%]) during period 2; this represented a significant decrease in death rate in period 2 (p = 0.002). In period 2, the main factors associated with an increased odds ratio of anaesthetic death were poor health status (ASA physical status classification) and old age. Species, gender, anaesthetic regimen, the nature and urgency of the procedure were not associated with risk. Conclusion and clinical relevance Following evidence based recommendations, the death rate related to anaesthesia was significantly decreased during period 2 compared to period 1. Application of evidence‐based medicine may contribute to an effective approach to decrease death rates. Other factors, not monitored in this study, may also have had an impact.